Secondary Metabolite Dereplication and Phylogenetic Analysis Identify Various Emerging Mycotoxins and Reveal the High Intra-Species Diversity in Aspergillus flavus - Uka, Valdet; Moore, Geromy G.; Arroyo-Manzanares, Natalia; Nebija, Dashnor; De Saeger, Sarah; Diana Di Mavungu, José (Frontiers in Microbiology, 2019)
Aspergillus flavus is one of the most important mycotoxigenic species from the genus Aspergillus, due to its ability to synthesize the potent hepatocarcinogen, aflatoxin B1. Moreover, this fungus is capable of producing several other toxic metabolites from the class of indole-tetramates, non-ribosomal peptides and indole-diterpenoids. Populations of A. flavus are characterized by considerable diversity in terms of morphological, functional and genetic features. Although for many years A. flavus was considered an asexual fungus, researchers have shown evidence that at best these fungi can exhibit a predominantly asexual existence. We now know that A. flavus contains functional genes for mating, uncovering sexuality as potential contributor for its diversification. Based on our results, we reconfirm that A. flavus is a predominant producer of B-type aflatoxins. Moreover, this fungus can decisively produce AFM1 and AFM2. We did not observe any clear relationship between mating-type genes and particular class of metabolites, probably other parameters such as sexual/asexual ratio should be investigated. A dynamic secondary metabolism was found also in strains intended to be used as biocontrol agents. In addition we succeeded to provide mass spectrometry fragmentation spectra for the most important classes of A. flavus metabolites, which will serve as identification cards for future studies. Both, metabolic and phylogenetic analysis proved a high intra-species diversity for A. flavus. These findings contribute to our understanding about the diversity of Aspergillus section Flavi species, raising the necessity for polyphasic approaches (morphological, metabolic, genetic, etc.) when dealing with this type of complex group of species.